Funny Stories For Six Years Old - "Paiba , Helen" (Macmillan Childrens Book: London, 1999)
A rich and varied selection of wonderfully entertaining stories by some of thevery best writers for children. perfect for reading alone or reading aloud and for dipping into time again."--Back cover
Keywords: Humorous stories